Analisis NDVI dan NDBI untuk Pemetaan Konversi Lahan di Kelurahan Napar, Kota Payakumbuh - Firma Maulidna; Sudrajat; Sri Rum Giyarsih (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2026)
The conversion of agricultural land to non-agricultural is an increasingly intensive phenomenon in urban and peri-urban areas, including in Napar Village, Payakumbuh City. This study aims to analyze changes in agricultural land cover and built-up land in the period 2015–2025 using the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Building Index (NDBI) methods as well as the additional extraction method Object-Based Image Analysis (OBIA). The data used were Landsat 8 and 9 images with a spatial resolution of 30 meters assisted by the results of Sentinel-2 image analysis with a resolution of 10 meters using the OBIA data extraction method to ensure changes in land objects. NDVI values with a range of 0.3–0.6 are categorized as agricultural land, while NDBI values >0.1 are categorized as built-up areas. The results of the analysis with images showed a significant decrease in the area of agricultural land followed by an increase in built-up areas, especially in zones with high accessibility near provincial roads and city centers. The NDVI and NDBI overlays revealed that the largest conversions occurred in the eastern and southern regions of Napar and the OBIA analysis clarified that there was a decrease in agricultural land area from 61 ha (2017) to 56 ha (2025) as a correction in NDVI results and followed by an increase in built-up land area from 27 ha (2017) to 36 ha (2025) as a correction in NDBI results using higher resolution image data. The main drivers of conversion include population growth, infrastructure development, and economic pressures. This study emphasizes the need for proper control of land use in maintaining a balance of land use and sustainable food sustainability.